2021
DOI: 10.3390/atmos12050551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assimilating Ground-Based Microwave Radiometer Data on the Precipitation Bifurcation Forecast: A Case Study in Beijing

Abstract: In this study, the temperature and relative humidity profiles retrieved from five ground-based microwave radiometers in Beijing were assimilated into the rapid-refresh multi-scale analysis and prediction system-short term (RMAPS-ST). The precipitation bifurcation prediction that occurred in Beijing on 4 May 2019 was selected as a case to evaluate the impact of their assimilation. For this purpose, two experiments were set. The Control experiment only assimilated conventional observations and radar data, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There has been considerable effort in developing retrieval techniques for ground-based MWRs, which, when applied to Numerical Weather Prediction (NWP), have shown accuracy levels comparable to those of radiosonde measurements [46]. Research incorporating MWR-derived profiles has underscored their utility in improving local weather forecasts [38,[47][48][49][50]. The RPG-HATPRO MWR system features 14 channels: 7 K-band channels dedicated to water vapor profile retrieval and 7 V-band channels (within the oxygen band) for temperature profile retrieval.…”
Section: Quality Controlmentioning
confidence: 99%
“…There has been considerable effort in developing retrieval techniques for ground-based MWRs, which, when applied to Numerical Weather Prediction (NWP), have shown accuracy levels comparable to those of radiosonde measurements [46]. Research incorporating MWR-derived profiles has underscored their utility in improving local weather forecasts [38,[47][48][49][50]. The RPG-HATPRO MWR system features 14 channels: 7 K-band channels dedicated to water vapor profile retrieval and 7 V-band channels (within the oxygen band) for temperature profile retrieval.…”
Section: Quality Controlmentioning
confidence: 99%
“…When utilized for Numerical Weather Prediction (NWP), MWR soundings have been found to exhibit accuracy on par with radiosonde soundings [49]. Several studies incorporating MWR retrieval profiles have demonstrated their potential in enhancing the forecast of local weather phenomena [50][51][52][53][54]. The RPG-HATPRO MWR system consists of 14 channels, which are divided into seven K-band channels for water vapor profile retrieval and seven V-band channels (oxygen band) for temperature profile retrieval.…”
Section: Agri Radiance and Mwr Datamentioning
confidence: 99%
“…The inversion software, provided by the MWR manufacturers, is utilized to generate level-2 products. These products include temperature and relative humidity profiles [54,55].…”
Section: Agri Radiance and Mwr Datamentioning
confidence: 99%
“…Meanwhile, when the sun is in the observation direction of the MWR, the BT data will be abnormally increased due to the influence of solar radiation, especially those used in low latitudes [14]. Therefore, it is essential to control the quality of the MWR observation data for a better forecast [15][16][17].…”
Section: Introductionmentioning
confidence: 99%